ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN DI BENGKEL PT. SUMBER TRADA MOTOR BANDAR LAMPUNG - Yusendra, Ariza Eka; -, KurniawanSyah (Jurnal Manajemen Magister Darmajaya, 2016)
The purpose of this study is to analyze customer satisfaction on services quality that have been provided by the workshop division of PT. Sumber Trada Motor Bandar Lampung. This type of research is descriptive quantitative used to describe the level of customer satisfaction of workshop services from PT. Sumber Trada Motor in Bandar Lampung and several initiatives to improve its services quality. Data collection techniques used were survey methods with questionnaires and the number of respondents who participated are 100 respondents. Analysis tools used to analyze the customer satisfaction on workshop Division of PT. Sumber Trada Motor are Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). From the studies that have been done, the value of CSI service quality in the workshop division PT Sumber Trada Motor Bandar Lampung is 51.11% which means customers feel quite satisfied with the quality of services that have been given by the company. While from IPA, in order to increase customer satisfaction even more, the workshop division of PT Sumber Trada Motor needs to improve the performance in the speed of handling consumer complaints, the ability to provide services quickly and correctly, the problem of increasing knowledge and employee skills, personalized attention to consumers, and the establishment of customer safety and convenience.Â Â Keywords: Customer Satisfaction, Costumer Satisfaction Index, Importance Performance Analysis